Leonardo's machines : Da Vinci's inventions revealed - Laurenza, Domenico; Taddei, Mario; Zanon, Edoardo (London : D&C, 2006)
Combines work from Leonardo da Vinci's original coded notebooks with modern computer imaging to piece together more than thirty of Leonardo's mechanical inventions.
Translation of: Macchine di Leonardo.
Includes bibliographical references (p. 239-240).
Young Adult
Keywords: Leonardo, -- da Vinci, -- 1452-1519 -- Knowledge -- Mechanical engineering; Leonardo, -- da Vinci, -- 1452-1519 -- Knowledge; Inventions -- History; Inventions -- History